Surface microstructure of thermoexfoliated graphite - Matzui, L.; Ovsienko, I.; Vovchenko, L.; Len`, T.; Shevchenko, N. (Functional Materials, 2005)
The surface microstructure of thermoexfoliated graphite (TEG) particles produced by thermoexfoliating graphite intercalation compounds with different intercalants of acceptor type at different temperatures has been investigated using optical microscopy and X-ray analysis. The surface microstructure has been found to depend essentially on the substance used as intercalant, the temperature of thermoexfoliation as well as particle sizes of initial graphite used for intercalation and thermoexfoliation. Вy varying intercalants and temperatures applied for thermoexfoliation, it is possible to obtain microstructures with the desired values of such parameters as grain sizes, uniformity and dispersity of grain structure on the developed surface of TEG. Методами оптической микроскопии и рентгеновского анализа исследована микроструктура поверхности частиц терморасширенного графита (ТРГ), полученного при разных температурах терморасширения интеркалированных соединений графита с разными интеркалянтами акцепторного типа. Показано, что упомянутая микроструктура существенно зависит от природы вещества-интеркалянта, температуры терморасширения и размеров частиц исходного графита. Варьированием типа интеркалянта и температуры терморасширения можно обеспечить необходимые значения параметров микроструктуры, таких, как размеры зерен, однородность и дисперсность зернистой структуры развитой поверхности ТРГ. Методами оптичної мiкроскопiї та рентгенiвського аналiзу дослiджено мiкроструктуру поверхнi частинок терморозширеного графiту, отриманого при рiзних температурах терморозширення з iнтеркальованих сполук графiту з рiзними iнтеркалянтами акцепторного типу. Показано, що згадана мiкроструктура iстотно залежить вiд природи речовини-iнтеркалянту, температури терморозширення та розмiрiв часток вихiдного графiту. Варiюванням типу iнтеркалянту i температури терморозширення можна забезпечити необхiднi значення параметрiв мiкроструктури, таких, як розмiри зерен, однорiднiсть i дисперснiсть зернистої структури розвитої поверхнi ТРГ.